TOURIST ATTRACTION OF WINTER CLIMATIC RESOURCES IN THE AGHSTEV VALLEY (Proceedings of the YSU C: Geological and Geographical Sciences, 2020)
The paper assesses the severity of climatic resources for the cold season and the comfort of climatic conditions for human health and activity. The possibility of the prospective use of climatic recreational resources of the cold period of the year, tourist attractiveness and ways of developing winter recreation is substantiated.
Keywords: cold season; climatic recreational resources; potential; tourist attractiveness; Aghstev Valley